Arranging Solar Energy For Farming Life: Designing A Solar Power Generation System As A Solution For Rice Field Irrigation In Kemulan Village, Turen District, Malang Regency - Prasetya, Luhur Adi; Rizaldy, Muhammad Ridha; Oktaviani, Herlina Ike; Ichwanto, Muhammad Aris; Wibowo, Satrio Adji; Rofiudin, Amir; Haq, Salsabila Thifal Nabil; Hendranawan, Rian Syahmulloh; Wibowo, Ary Agung; Widiyawati, Irva; Muttaqiyah, Khusnul; Permataningtyas, Anisa; Samodra, Joko (Institute Of Advanced Knowledge and Science, 2025)
This research aims to design and test a solar power generation system (PLTS) as an alternative energy solution for agricultural irrigation in Kemulan Village, Turen District, Malang Regency. The method used is Research and Development (R&D) with the 4D model: Define, Design, Develop, and Disseminate. The define stage shows that farmers experience limited access to energy and high irrigation costs, with an average daily energy requirement of 1,500 Wh and operational costs of Rp 300,000-500,000 per season. Based on this data, a solar PV system was designed using two 100 Wp solar panels, a 12V DC pump, and an MPPT controller. Simulation through PVsyst showed an energy output of 1,620 Wh/day, while field testing produced 1,560 Wh/day with a water discharge of 70 liters/minute. Expert validation results show the system has high efficiency (86-88%), is easy to operate, and has the potential to be replicated. End-user evaluations showed positive scores on the aspects of convenience, usefulness, and re-adoption intention. The findings prove that a local needs-based approach and active involvement of farmers in the design to evaluation process can produce renewable technology systems that are applicable, efficient, and socially acceptable in the rural agricultural sector.